Risk, commercialism and social purpose: Repositioning the English housing association sector. (July 2018) - Manzi, Tony; Morrison, Nicky
Originally seen as the 'third arm' of UK housing policy, the independent, not-for-profit housing association sector had long been seen as effective in 'filling the gap' where the state or market were unable to provide for households in need. Since the 1980s in particular, successive governments had viewed housing associations in favourable terms as efficient, semi-autonomous social businesses, capable of leveraging significant private funding. By 2015, in contrast, central government had come to perceive the sector as inefficient, bureaucratic and wasteful of public subsidy. Making use of institutional theory, this paper considers this paradigm shift and examines the organisational responses to an increasingly challenging operating environment. By focusing, in particular, on large London housing associations, the paper analyses their strategic decision-making to address the opportunities and threats presented. The paper argues that in facing an era of minimal subsidy, low security and high risk, the 2015 reforms represent a critical juncture for the sector. Housing organisations face a stark dilemma about whether to continue a strategy of 'profit for purpose' or to embrace an unambiguously commercial ethos. The article contends that the trajectory of decision-making (although not unidirectional) leads ultimately towards an increased exposure to risk and vulnerability to changes in the housing market. More fundamentally, the attempt to reconcile social and commercial logics is likely to have wider consequences for the legitimacy of the sector.